Library Management Software Packages: A Case Study of Central University of Jammu and SMVDU-Katra - Kumar, Sudesh; Gupta, Sangita (International Journal of Computer Sciences and Engineering, 2025)
Due to the changing scenario of the 21st century and because of the rapid advancement in the information technology, the role of university librarian has become very vital and significant. Automation and digitization of the libraries have become an essential factor for achieving the objectives of the users of the present and future generations. During the past decade we have seen many changes around the world in the library and information field. Various libraries and information centers are managed to improve their efficiency, capability, services and productivity by using the latest technologies. This study has been presented with the types of library management software packages being used in the Central University of Jammu and Shri Mata Vaishno Devi University (SMVDU) - Katra. The main purpose of the study is to provide some basic idea to librarians which help them in selecting the suitable library management software package for their respective libraries